Improvement on simulating TCP connection establishment in NS2 - Yu JIANG; Jian REN; Li-ming ZHOU (Tongxin xuebao)
In the procedure of three-way handshake of transmission control protocol connection establishment,it involves the management of half-connection and connection tables.However,in the famous networks simulator NS2,there is only a formal description instead of a concrete and complete implementation for the procedure of TCP connection establishment.An improvement was beed made on the point.Table structures for half-connections and connections are added,and the way of managing half-connection table in Linux kernel is also imported into NS2.Simulation results show that it is clear to monitor the change in half-connection table in the TCP connection establishment procedure,and thus the requirement of simulating the connection establishment procedure in studies such as protection from TCP SYN flooding attack can be met.